2007
DOI: 10.1152/physiolgenomics.00066.2007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the circadian transcriptome in adult mouse skeletal muscle

Abstract: Circadian rhythms are approximate 24-h behavioral and physiological cycles that function to prepare an organism for daily environmental changes. The basic clock mechanism is a network of transcriptional-translational feedback loops that drive rhythmic expression of genes over a 24-h period. The objectives of this study were to identify transcripts with a circadian pattern of expression in adult skeletal muscle and to determine the effect of the Clock mutation on gene expression. Expression profiling on muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
296
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 319 publications
(328 citation statements)
references
References 73 publications
29
296
0
3
Order By: Relevance
“…The loss of circadian expression of MyoD in skeletal muscle from both Clock Δ19 and Bmal1 −/− mice is very similar to what has been previously observed with other genes known to be regulated by BMAL1 and CLOCK, such as Per2 and Dbp (referred to as clock-controlled genes) (7,8). Results from reporter gene assays and ChIP experiments confirmed that MyoD is a direct target of CLOCK and BMAL1.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The loss of circadian expression of MyoD in skeletal muscle from both Clock Δ19 and Bmal1 −/− mice is very similar to what has been previously observed with other genes known to be regulated by BMAL1 and CLOCK, such as Per2 and Dbp (referred to as clock-controlled genes) (7,8). Results from reporter gene assays and ChIP experiments confirmed that MyoD is a direct target of CLOCK and BMAL1.…”
Section: Discussionsupporting
confidence: 84%
“…MyoD is a wellestablished skeletal muscle-specific transcription factor that directly regulates expression of the myogenic program (9). In addition to MyoD, we found that the core components of the molecular clock, including Bmal1 and Per2 expression, were oscillating as is seen in liver and other peripheral tissues (7). Interestingly, MyoD expression, like Per2 mRNA, did not oscillate in muscle of the Clock Δ19 mutant mouse, suggesting the possibility that MyoD is a clock-controlled gene.…”
mentioning
confidence: 67%
See 3 more Smart Citations